Prevalence of overweight in children and adolescents with attention deficit hyperactivity disorder and autism spectrum disorders: a chart review - Tybor David J; Perrin Ellen C; Bandini Linda G; Curtin Carol; Must Aviva (BMC, 2005)
Abstract Background The condition of obesity has become a significant public health problem in the United States. In children and adolescents, the prevalence of overweight has tripled in the last 20 years, with approximately 16.0% of children ages 6-19, and 10.3% of 2-5 year olds being considered overweight. Considerable research is underway to understand obesity in the general pediatric population, however little research is available on the prevalence of obesity in children with developmental disorders. The purpose of our study was to determine the prevalence of overweight among a clinical population of children diagnosed with attention deficit hyperactivity disorder (ADHD) and autism spectrum disorders (ASD). Methods Retrospective chart review of 140 charts of children ages 3-18 years seen between 1992 and 2003 at a tertiary care clinic that specializes in the evaluation and treatment of children with developmental, behavioral, and cognitive disorders. Diagnostic, medical, and demographic information was extracted from the charts. Primary diagnoses of either ADHD or ASD were recorded, as was information on race/ethnicity, age, gender, height, and weight. Information was also collected on medications that the child was taking. Body mass index (BMI) was calculated from measures of height and weight recorded in the child's chart. The Center for Disease Control's BMI growth reference was used to determine an age- and gender-specific BMI z-score for the children. Results The prevalence of at-risk-for-overweight (BMI >85th%ile) and overweight (BMI > 95th%ile) was 29% and 17.3% respectively in children with ADHD. Although the prevalence appeared highest in the 2-5 year old group (42.9%ile), differences among age groups were not statistically significant. Prevalence did not differ between boys and girls or across age groups (all p > 0.05). For children with ASD, the overall prevalence of at-risk-for-overweight was 35.7% and prevalence of overweight was 19%. Conclusion When compared to an age-matched reference population (NHANES 1999-2002), our estimates indicate that children with ADHD and with ASD have a prevalence of overweight that is similar to children in the general population.